Pemetaan pengetahuan terhadap perkembangan penelitian kebutuhan informasi pada database Scopus menggunakan VOSViewer - Ananda, Yonna; Rizal, Edwin; Rohman, Asep Saeful (Jurnal Informatio, 2025)
Information need is a cognitive condition where individuals seek relevant information to support decision-making and fulfill specific needs. Understanding information needs is crucial for comprehending information-seeking and use behaviors, especially in the increasingly complex digital age. This study aims to map the development of publications related to information needs, identify research trends and relationships between scientific concepts, as well as author collaboration networks (co-authorship) and keywords. This mapping is beneficial for academics, policymakers, and information professionals. This quantitative descriptive study employed a bibliometric approach, analyzing 3,941 English-language documents indexed in Scopus from 2014 to 2024, using the keyword "information needs." Results indicate a publication increase until 2021, followed by a decline, potentially linked to research focus shifts and the impact of the Covid-19 pandemic. The journal "Library Philosophy and Practice" affirms its significant role in academic discourse. Author collaboration networks demonstrate intense cooperation among researchers from various institutions and countries. Research focuses on information needs, decision-making, and information retrieval, with a significant response to global issues. Keyword visualization reveals a close relationship between information needs, technology, and human behavior. This study concludes that information need is a multidimensional topic with significant contributions across disciplines, offering opportunities for further research, particularly in health information literacy.